Accounting as A Representational Craft: Reflexive Accounting Research - Yee, Cheok Mui; Khin, Edward Wong Sek (Asian Journal of Accounting Perspectives, 2011)
This article discusses the scope of managerial accounting research based on agency theory, that is, behavioural decision-making, the use of capital markets and what is called positive theory. The authors believe that management accounting representations are somewhat stable, and, therefore, allow accounting researchers to theorise the form and function of representations in the organisation from a wide variety of perspectives, such as organisation theory, social theory, and corporate and manufacturing strategies. In order to justify the above analysis, the authors refer to the way in which the structuration theory of Anthony Giddens, that has been employed by Macintosh & Scapens, argues that management accounting systems are interpretive schemes, facilities and norms used by management to make plans, take action and control others in an organisation.